Congenital Mediastinal Neuroenteric Cyst as a cause of respiratory distress since birth - Gillani, Saima; Muhammad Junaid Khan; Faiza Akram; Anis-ur-Rehman; Raabiya Shahjahan (Journal of the Pakistan Medical Association, 2022)
Mediastinal Neuroenteric Cyst is a rare congenital presentation in infants and is associated with a high mortality rate. It is a very uncommon benign lesion and usually develops from abnormal embryological development of the foregut. Till now, only 106 cases have been reported worldwide. In Pakistan only three cases have been published, with varying presentations. The clinical presentation and age at presentation vary from asymptomatic and coincidental finding on chest x-ray, to limb numbness or early presentation with severe symptoms like those in our case. In fact, it poses an important challenge for paediatricians. We present a rare case with emphasis on clinical presentation and diagnostic criteria. Keywords: Respiratory Distress; Congenital Bronchogenic Cyst; Foregut Duplication; Congenital Neuroenteric Cyst; Lobar Pneumonia.